Mountain Hospitals in the Eastern Pyrenees: Mapping the welfare spaces of the Middle Ages (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
Our proposal focuses on the characterisation of the ‘areas of assistance’ (AA) that developed in the high Pyrenean valleys during the passage from Antiquity to the Middle Ages. In this process, we take into account three types of facilities: baths with a Roman tradition, hospitals documented for the Middle Ages and Marian sanctuaries, of uncertain origin, where the survival of pre‐Christian cults is usually of some importance. The link that we have established between these three elements allows us to draw up a series of areas of assistance, located at strategic points on the roads and also related to the high mountain animal husbandry. The cartography that we generate, using GIS tools, highlights a certain geographical pattern in the location of these areas and in the facilities that characterise them, and shows the continuity of these spaces since antiquity. At the same time, we relate these areas of assistance to high mountain productive activities and not exclusively to the passage of travellers, as has often been claimed.
Keywords: ENG